CoSP approach for the synthesis of blue MoO3 nanoparticles for application as hole transport layer (HTL) in organic solar cells. (1st March 2018) - Dwivedi, Charu; Mohammad, Tauheed; Bharti, Vishal; Patra, Asit; Pathak, Sandeep; Dutta, Viresh
Highlights: In this manuscript, we have found Continuous Spray Pyrolysis (CoSP) as a new technique to develop MoO3 nanoparticles. This is a totally new route which has not been reported earlier for the synthesis of MoO3 . The technique is low cost, time consuming and a continuous process in which large amount of nanoparticles can be synthesized at a time. Unique properties of the material synthesized have been found with the change in the process parameters. Abstract: The synthesis of MoO3 nanoparticles is reported using a Continuous Spray Pyrolysis (CoSP) reactor and the influence of zone temperature, precursor concentration on the structural and morphological properties is investigated. The collected nanoparticles are utilized to prepare thin films by spin coating and further annealing at various temperatures. The improvement in morphology, crystallinity and the band gap shift shows the effectiveness of the annealing treatment in creating a proper hole transport layer for device applications. The technique thus allows the film formation using a non-vacuum method well suited for organic solar cells. The CoSP based MoO3 (CoSP_MoO3 ) films are demonstrated to have equal performance to hole-injection layers composed of thermally evaporated MoO3 (eMoO3 ).